Factors associated with costs and health outcomes in patients with Back and leg pain in primary care: a prospective cohort analysis - Jesse Kigozi; Kika Konstantinou; Reuben Ogollah; Kate Dunn; Lewis Martyn; Susan Jowett (BMC, 2019)
Abstract Background There is limited research on the economic burden of low back-related leg pain, including sciatica. The aim of this study was to describe healthcare resource utilisation and factors associated with cost and health outcomes in primary care patients consulting with symptoms of low back-related leg pain including sciatica. Methods This study is a prospective cohort of 609 adults visiting their family doctor with low back-related leg pain, with or without sciatica in a United Kingdom (UK) Setting. Participants completed questionnaires, underwent clinical assessments, received an MRI scan, and were followed-up for 12-months. The economic analysis outcome was the quality-adjusted life year (QALY) calculated from the EQ-5D-3 L data obtained at baseline, 4 and 12-months. Costs were measured based on patient self-reported information on resource use due to back-related leg pain and results are presented from a UK National Health Service (NHS) and Societal perspective. Factors associated with costs and outcomes were obtained using a generalised linear model. Results Base-case results showed improved health outcomes over 12-months for the whole cohort and slightly higher QALYs for patients in the sciatica group. NHS resource use was highest for physiotherapy and GP visits, and work-related productivity loss highest from a societal perspective. The sciatica group was associated with significantly higher work-related productivity costs. Cost was significantly associated with factors such as self-rated general health and care received as part of the study, while quality of life was significantly predicted by self-rated general health, and pain intensity, depression, and disability scores. Conclusions Our results contribute to understanding the economics of low back- related leg pain and sciatica and may provide guidance for future actions on cost reduction and health care improvement strategies. Trial registration 13/09/2011 Retrospectively registered; ISRCTN62880786.